Defining the scope of materials for demand-driven material requirements planning : A case study in operative purchasing of an MNC - Jaakkola, Tuomas Konstantin (My University, 2023)
In today's fast-paced business environment, effective material planning is crucial for companies with manufacturing activities to improve their operations, or even remain competitive. De-mand-driven MRP (DDMRP) is an approach to material planning that emphasizes responsive-ness to customer demand, allegedly resulting in the improvement of material flow. The aim of this research is to determine which proportion of purchased materials could be beneficial to purchase with planning done in a demand-driven way in a complex manufacturing environ-ment, and what the financial impact of implementing DDMRP would be. The structure of the theoretical framework is formed on the themes of DDMRP, suitability identification tools, and profitability. The topic areas are reviewed from the perspective of the operative purchasing department located in a manufacturing plant of a multinational company. The research problems are approached with three different questions about suitability, fea-tures of the identification tool, and financial impact. The objective of this study is to address existing study gaps by defining what materials are DDMRP-suitable and building a tool that helps to identify such materials. Furthermore, the research problem of financial impact origi-nating from DDMRP implementation is addressed to form a comprehensive image of the im-plementation process of DDMRP. The study focuses solely on purchased materials. The research methodology consists of a mixed method case study approach, where semi-structured interviews were conducted with supply chain professionals from the case company, and quantitative data related to the case company's operations was analyzed. The quantitative analysis was done with the help of an Excel calculation sheet, that simulated DDMRP buffers for the sample materials. The data consisted of the relevant data of over 10,000 purchased materi-als. The findings of this study suggest that there are no certain characteristics that materials suitable for DDMRP have, but the potential must be defined individually in the case of every purchased material. The tool initially developed in this study helps to identify materials that meet the requirement of providing potential positive financial impact if brought into DDMRP scope by analyzing historical demand data, lead times, and inventory carrying costs. The results of this study provide insights for supply chain professionals on how to identify ma-terials that could have a positive effect from demand-driven planning. The tool developed in this study can be used by companies to analyze their material procurement process and identi-fy areas for improvement. This study contributes to the field of supply chain management by providing a practical tool for companies to understand DDMRP phenomena and improve their material planning. Limiting factors of the research include data accuracy and the employment of the tool as an aid for decision-making only.

Nykypäivän nopeatempoisessa liiketoimintaympäristössä tehokas materiaalisuunnittelu on ratkaisevan tärkeää valmistavan teollisuuden yrityksille toimintansa parantamiseksi ja pel-kästään kilpailukykynsä säilyttämiseksi. Kysyntävetoinen materiaalitarpeiden suunnittelu (DDMRP) on kohtalaisen uusi, kysyntävetoisuutta painottava lähestymistapa materiaali-suunnitteluun, jonka väitetään vähentävän ylivarastoinnin ja varaston loppumisen riskiä. Tämän tutkimuksen tavoitteena on selvittää, mikä osuus ostetuista materiaaleista voisi olla hyödyllistä ostaa kysyntälähtöisesti monimutkaisessa teollisessa ympäristössä, ja mikä olisi DDMRP:n käyttöönoton taloudellinen vaikutus. Teoreettisen viitekehyksen rakenne muo-dostuu DDMRP:n, soveltuvuuden tunnistamisen työkalujen ja kannattavuuden teemoista. Aihealueita tarkastellaan monikansallisen yrityksen tuotantolaitoksessa sijaitsevan opera-tiivisen oston näkökulmasta. Tutkimusongelmia lähestytään kolmella eri kysymyksellä, jotka liittyvät soveltuvuuteen, tunnistamistyökalun ominaisuuksiin ja taloudellisiin vaikutuksiin. Tämän tutkimuksen ta-voitteena on käsitellä aukkoja aiheeseen liittyvässä tutkimuksessa, määrittelemällä DDMRP:hen sopivien materiaalien laajuus ja rakentamalla työkalu, joka auttaa tällaisten materiaalien tunnistamisessa. Lisäksi DDMRP:n käyttöönottoon liittyviin taloudellisiin vai-kutuksiin liittyvän tutkimusongelman tarkoituksena on muodostaa kattava kuva DDMRP:n toteutusprosessista. Tutkimus keskittyy pelkästään ostettaviin materiaaleihin. Tutkimusmetodologia koostuu sekamenetelmäisestä tapaustutkimuksesta, johon sisältyi puolistrukturoituja haastatteluja case-yrityksen ammattilaisten kanssa ja case-yrityksen toimintaan liittyvän määrällistä datan analysointia. Kvantitatiivinen analyysi tehtiin Excel-laskentataulukon avulla, joka simuloi DDMRP-puskureita otoksen materiaaleille. Data koos-tui yli 10 000 ostettavan materiaalin datasta. Tämän tutkimuksen tulokset viittaavat siihen, että ei ole olemassa tiettyjä ominaisuuksia, joita DDMRP:hen sopivilla materiaaleilla on, vaan potentiaali on määriteltävä erikseen jokaisen materiaalin kohdalla. Tässä tutkimukses-sa alustavasti kehitetty työkalu auttaa tunnistamaan materiaaleja, jotka täyttävät vaatimuk-sen mahdollisten positiivisten taloudellisten vaikutusten tarjoamisesta DDMRP:n piiriin tuotaessa. Työkalu tunnistaa sopivat materiaalit analysoimalla historiallisia kysyntätietoja, tilausaikoja ja varastointikustannuksia. Tämän tutkimuksen tulokset tarjoavat oivalluksia toimitusketjujen ammattilaisille siitä, miten tunnistaa materiaalit, joilla voisi olla positiivinen vaikutus kysyntälähtöiseen suun-nitteluun. Tässä tutkimuksessa kehitetyn työkalun avulla yritykset voivat analysoida mate-riaalihankintaprosessiaan ja tunnistaa parannuskohteita. Tämä tutkimus edistää toimitus-ketjun hallintaa tarjoamalla käytännön työkalun ymmärtää DDMRP:tä ja parantaa materiaa-lisuunnitteluaan.
Keywords: toimitusketjut; materiaalit; suunnittelu; tilaukset; varastokirjanpito; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management